RELATIONSHIP ANALYSIS OF WORK MOTIVATION AND PARTICIPATIVE LEADERSHIP TO UNDERSTAND FUNCTIONAL EMPLOYMENT BEHAVIOR - Abdul Rivai (Universitas Labuhanbatu, 2021)
This study aims to determine and understand the relationship between work motivation and participatory leadership with the work behavior of the Functional Staff of the Education and Culture Office of East Nusa Tenggara Province because the Province of East Nusa Tenggara is one of the provinces whose development and growth is relatively slower compared to other provinces in Indonesia. The study population was the functional staff who did not have a structural position of 94 people. Samples were taken as many as 75 people. Data collection using a questionnaire instrument.Based on hypothesis testing, this study found: (1) there was a relationship between work motivation and work behavior in which work motivation contributed 49.29% to work behavior, (2) there was a positive relationship between participative leadership and work behavior in which participative leadership contributed 51.49% of work behavior, and there is a positive relationship between work motivation and participatory leadership together with work behavior. Where work motivation and participatory leadership together contribute 67.01% to work behavior. From the three findings, the conclusions of this study are stated that: (a) Work behavior provides a good relationship to increase work motivation, (b) Work behavior can be improved by considering participatory leadership, by involving employees in every decision making, respecting opinions and proposals employees, and enhance collaboration.